Implementasi Program Diklat Pemberdayaan Masyarakat (DPM) dalam Peningkatan Kompetensi Masyarakat Pesisir oleh Politeknik Pelayaran Sumatera Barat - Richa Anggelina; Rahmadhona Fitri Helmi (YASIN, 2025)
Enhancing the capacity of coastal communities in the field of maritime navigation is a strategic effort to support national maritime development. One such initiative is the Diklat Pemberdayaan Masyarakat (DPM) program organized by the Politeknik Pelayaran Sumatera Barat. This study aims to analyze the implementation of the DPM program using the policy implementation model developed by George C. Edwards III, which includes four key variables: communication, resources, disposition of implementers, and bureaucratic structure. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The research focused on evaluating the effectiveness of the program in reaching coastal communities as the primary target group. The findings indicate that the DPM program has been implemented with a fair degree of effectiveness, as evidenced by high community participation and strong field-level commitment. All four variables in Edwards’s model contributed positively to the implementation, although challenges remain—such as participants’ limited understanding of the training material and inconsistencies in recruitment information. The main supporting factors for the program’s success were the flexibility and proactive attitude of its implementers. The study concludes that the DPM program has successfully improved maritime skills among coastal populations; however, improvements in coordination and adaptive implementation are needed to ensure the program’s sustainability and long-term effectiveness.